Efficacy and safety of abiraterone acetate plus prednisolone in patients with early metastatic castration-resistant prostate cancer who failed first-line androgen-deprivation therapy: a single-arm, phase 4 study. (15th December 2020) - Kobayashi, K; Okuno, N; Arai, G; Nakatsu, H; Maniwa, A; Kamiya, N; Satoh, T; Kikukawa, H; Nasu, Y; Uemura, H; Nakashima, T; Mikami, K; et al.
Abstract: Aim: The aim was to evaluate the efficacy and safety of abiraterone acetate plus prednisolone in patients with chemotherapy-naïve early metastatic castration-resistant prostate cancer who failed first-line androgen deprivation therapy. Methods: Patients with early metastatic castration-resistant prostate cancer with confirmed prostate-specific antigen progression within 1-year or prostate-specific antigen progression without having normal prostate-specific antigen level (<4.0 ng/mL) during first-line androgen deprivation therapy were enrolled and administered abiraterone acetate (1000 mg) plus prednisolone (10 mg). A minimum of 48 patients were required according to Simon's minimax design. The primary endpoint was prostate-specific antigen response rate (≥50% prostate-specific antigen decline by 12 weeks), secondary endpoints included prostate-specific antigen progression-free survival and overall survival. Safety parameters were also assessed. Results: For efficacy, 49/50 patients were evaluable. Median age was 73 (range: 55–86) years. The median duration of initial androgen deprivation therapy was 32.4 (range: 13.4–84.1) weeks and 48 patients experienced prostate-specific antigen progression within 1-year after initiation of androgen deprivation therapy. prostate-specific antigen response rate was 55.1% (95% confidence interval: 40.2%–69.3%), median prostate-specific antigen–progression-free survival was 24.1 weeks, and median overall survival was 102.9 weeks (95% confidence interval: 64.86 not estimable [NE]). Most common adverse event was nasopharyngitis (15/50 patients, 30.0%). The most common ≥grade 3 adverse event was alanine aminotransferase increased (6/50 patients, 12.0%). Conclusions: Abiraterone acetate plus prednisolone demonstrated a high prostate-specific antigen response rate of 55.1%, suggesting tumor growth still depends on androgen synthesis in patients with early metastatic castration-resistant prostate cancer. However, prostate-specific antigen–progression-free survival was shorter than that reported in previous studies. Considering the benefit–risk profile, abiraterone acetate plus prednisolone would be a beneficial treatment option for patients with chemotherapy-naive metastatic prostate cancer who show early castration resistance. Abstract : This study investigated efficacy and safety of abiraterone acetate plus prednisolone in chemotherapy-naive early metastatic castration-resistant prostate cancer patients. Abiraterone acetate plus prednisolone proved to be a beneficial treatment option with regards to its higher response rate.